Traktat matematyczny "Geometra Polski" Stanisława Solskiego - początki polskiego dyskursu naukowo-dydaktycznego = The Mathematical Treaty "Geometra Polski" by Solski - the beginnings of Polish scientific discourse - Biniewicz, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication of "Geometra Polski" in 1683-1686 was a very important step forward in the development of the Polish scientific discourse. Stanisław Solski, the author of "Geometra", was a Jesuit, who wrote a treaty for researchers and crafters or land surveyors. The article is about the text which is the first complete Polish course of geometry and mathematics.
Keywords: początek polskiego dyskursu naukowego; traktat matematyczny; komunikacja naukowa; beginning of Polish scientific discourse; textbook of mathematics; scientific communication